Analysis of Gender Inequality in Poverty Reduction Program - Walid Walid; Bayu Rizky Pratama (Economics Development Analysis Journal, 2020)
This study will focus on developing research in descriptive and inferential analysis of gender equality in poverty alleviation in the province of Central Java. This analysis is expected to provide input for advocacy on poverty alleviation programs, look at gender equality factors, provide input for monitoring the implementation of poverty alleviation programs, especially in Central Java, which can be used as a reference in national level policy making. This type of research uses a combination of descriptive and inferential research that uses secondary data from BPS and other sources. The technique used in collecting data in this study is the documentation study conducted by collecting secondary data, recording and processing data related to this research. The data analysis technique used is the panel data regression model and correlation analysis. The result obtained is that poverty alleviation programs in Central Java still contain the influence of gender disparity. The gender gap referred to is contained in the variables IPG, IDG, HDI, TKWP and SPP whose influence and relationship with poverty levels in Central Java in the past five years.